Integrating Ergonomics with Lean Six Sigma on a meal solutions industrial kitchen - Carvalho, Claudia Sofia Costa (2016)
The integration of Ergonomics with Lean and Six Sigma are the foundations of this dissertation. Lean Six Sigma (LSS) philosophy has already proven its worth through several successful implementations in the most varied kind of industry. Several researchers are complementing Lean Six Sigma values and prepositions with other disciplines, so that improvement doesn’t concern only the processes flow, but also the entire ecosystem with it. Therefore, Ergonomics integrates perfectly with LSS, not only in a sense of concerning about employees while LSS concerns about processes, but also helping to improve efficiency. It should be integrated on the core of every company’s management team. This dissertation focuses on studying the production system of an Industrial Kitchen which produces ready-to-eat (RTE) meals for Pingo Doce retailer. The aim was to apply Ergonomics, Lean and Six Sigma’s principles in an integrated form, in order to improve the Kitchen’s productivity and efficiency. The HACCP standards are crucial in a food industry of this kind so were, therefore, considered at all times. The methodology utilized was a holistic approach of the DMAIC cycle, including Ergonomics in all stages and HACCP especially in the Improve phase. This case study brought added value to the company by achieving the initially proposed goals, regarding elimination of waste and productivity increase by 16% in 2015 vs 2014 results, always focusing on the well-being of employees. The operational costs decreased 18%, overcoming the initially set goal of 6%. Developing this project has made it possible to understand the applicability of the utilized methodology and the impact it may have in all kinds of industries, as well as its limitations. The DMAIC cycle, together with all the other LSS implemented tools, proved their worth when it comes to planning and implementing a project of this kind. They are simple to apply and highly effective. The approached theme – and the integration of other disciplines with LSS – should be applied in different industries, so that broader conclusions can be made while continuously improving the implementation strategy and proving its value.